Performance validation of the KeraSkin™ reconstructed human epidermis (RhE) model according to OECD document no. 219 and exploratory optimization of its predictive capacity for in vitro skin corrosion testing - JunHo Park; Hayan Jeong; Seohwi Yoon; Yongbin Lee; Jung Eun Park; Su-Hyon Lee; Seolyeong Kim; Eunjin Byeon; Jungkwan Seo; Suejin Kim; Bong-Gun Ju; Sang Hee Lee; et al. (Toxicology in Vitro, 2026)

Preferential and synergistic arsenate–phosphate retention by porous biochar revealed by depth profiling X-ray photoelectron spectroscopy - Junho Han; Seoyeon Lee; Minhee Kim (Journal of Environmental Chemical Engineering, 2026)

How long will perfluoroalkyl substances persist in sludge-amended soils?: Century-scale regional accumulation-decay modeling for North America, Europe, and Asia - Minhee Kim; Seunghun Hyun; Junho Han (Journal of Hazardous Materials, 2026)

Historical and future water quality risks driven by climate change: Strategic management and overcoming challenges - Minhee Kim; Min Jang; Choe Earn Choong; Junho Han (Water Research, 2026)

Digestive ripening and fragmentation of goethite nanorods into nanospheres under natural wet-dry cycles: Unveiling hidden nanocolloid mobilization to water system - Junho Han; Evert J. Elzinga; Minhee Kim (Water Research, 2025)

Multi-Enzyme Supplementation to Diets Containing 2 Protein Levels Affects Intramuscular Fat Content in Muscle and Modulates Cecal Microflora Without Affecting the Growth Performance of Finishing Pigs - Qianqian Zhang; Sungbo Cho; Junho Song; Jinuk Jeong; Minjae Yu; Seyoung Mun; Kyudong Han; In Ho Kim (Probiotics and Antimicrobial Proteins, 2025)

Integrating bioaccessibility into human health risk assessment: Stabilization approach of smelter-contaminated soil with natural organic amendments - Minhee Kim; Jong-Sung Kim; Hee-Myong Ro; Junho Han (Journal of Environmental Management, 2025)

Phosphate sorption mechanisms in biochar: Insights from depth profiling of porous structure across pH and pyrolysis conditions - Junho Han; Seoyeon Lee; Seunghun Hyun; Minhee Kim (Bioresource Technology, 2025)

Understanding delamination behavior of air electrode in solid oxide electrolysis cells through in situ monitoring of internal oxygen partial pressure - Han Hwi Kim; Minuk Kim; Junsu Lee; Junho Park; Jun-Young Park; Xia-Dong Zhou; Hyung-Tae Lim (Chemical Engineering Journal, 2025)

Nationwide profiling and source identification of organophosphate esters in Korean surface waters using target, suspect, and non-target HRMS analysis - Daeho Kang; Heewon Jang; Sori Mok; Jun Yub Kim; Younghun Choi; Sun-Hong Lee; Sojeong Han; Tae Jin Park; Hyo-Bang Moon; Junho Jeon (Chemosphere, 2024)

Causative mechanisms limiting the removal efficiency of short-chain per- and polyfluoroalkyl substances (PFAS) by activated carbon - Junho Han; Choe Earn Choong; Min Jang; Junghee Lee; Seunghun Hyun; Won-Seok Lee; Minhee Kim (Chemosphere, 2024)

Determination of submicron aerosols effective density using two-stage low-pressure impactor and aerosol electrometer based on pre-measured particle size distribution - Jaeho Oh; Jangseop Han; Junho Hyun; Geun-young Park; Jungho Hwang (Journal of Hazardous Materials, 2024)

Treatment techniques for removal of polybrominated diphenyl ethers (PBDEs) from real wastewater: Limitations, challenges, and future research directions - Minhee Kim; Junho Han (Journal of Water Process Engineering, 2024)

Synergistic effect of climate change and water management: Historical and future soil salinity in the Kur-Araz lowland, Azerbaijan - Junho Han; Minhee Kim; Zaman Mammadov; Seoyeon Lee; Evert J. Elzinga; Garib Mammadov; Wonjae Hwang; Hee-Myong Ro (Science of The Total Environment, 2024)

Highly efficient oxidation of single-walled carbon nanotubes in liquid crystalline phase and dispersion for applications in Li-ion batteries - Jung Hoon Kim; Junho Ahn; Han-Min Kim; Joon Young Cho; Do Geun Lee; Youngseok Oh; Jong Hwan Park; Jin Soo Kim; Jung-Keun Yoo; Joong Tark Han (Chemical Engineering Journal, 2023)

Spatial distribution of salinity and heavy metals in surface soils on the Mugan Plain, the Republic of Azerbaijan - Junho Han; Zaman Mammadov; Minhee Kim; Elton Mammadov; Seoyeon Lee; Jisuk Park; Garib Mammadov; Guliyev Elovsat; Hee-Myong Ro (Environmental Monitoring and Assessment, 2021)

Factors modifying the structural configuration of oxyanions and organic acids adsorbed on iron (hydr)oxides in soils. A review - Junho Han; Minhee Kim; Hee-Myong Ro (Environmental Chemistry Letters, 2020)
Oxyanions are ubiquitous in soils, organisms and the environment. Due to their unique chemical structure, oxyanions can be easily transferred into other systems. Carbonate (CO 3 2− ), nitrate (NO 3 − ), phosphate (PO 4 3− ), silicate (SiO 4 2− ) and sulfate (SO 4 2− ) are the major oxyanions in organisms and the soil environment, whereas arsenate (AsO 4 3− ), antimonate (SbO 4 3− ), borate (BO 3 3− ), selenate (SeO 4 2− ), and tellurate (TeO 4 2− ) are generally reported as toxic chemicals found at trace levels. Excessive oxyanions leached from soils into water have caused severe environmental problems. Here, we review the factors affecting the structural configuration of oxyanions and organic acids adsorbed on iron oxides and hydroxides. The configuration of oxyanions on iron (hydr)oxides is controlled by surface loading, pH, sample phase, competing ions and organic acids. Under conditions of low surface loading and low pH at the interface in the absence of competing ions, oxyanions with high affinity possibly form a complex with higher denticity. But an increase in pH decreases the number of sorption sites; thus, a transition from a tri- or bidentate complex to monodentate and outer-sphere complexes occurs.

Design, synthesis, and biological evaluation of polyphenols with 4,6-diphenylpyrimidin-2-amine derivatives for inhibition of Aurora kinase A - Young Han Lee; Jihyun Park; Seunghyun Ahn; Youngshim Lee; Junho Lee; Soon Young Shin; Dongsoo Koh; Yoongho Lim (DARU Journal of Pharmaceutical Sciences, 2019)

Interpreting competitive adsorption of arsenate and phosphate on nanosized iron (hydr)oxides: effects of pH and surface loading - Junho Han; Hee-Myong Ro (Environmental Science and Pollution Research, 2018)

Fluxes of nutrients and trace metals across the sediment-water interface controlled by sediment-capping agents: bentonite and sand - Junho Han; Hee-Myong Ro; Kyung Hwa Cho; Kyoung-Woong Kim (Environmental Monitoring and Assessment, 2016)

Chemical extractability of As and Pb from soils across long-term abandoned metallic mine sites in Korea and their phytoavailability assessed by Brassica juncea - Junho Han; Juhee Kim; Minhee Kim; Deok Hyun Moon; Jung-Suk Sung; Seunghun Hyun (Environmental Science and Pollution Research, 2015)

Flow Dynamics of $$\hbox {CO}_{2}$$ CO 2 /brine at the Interface Between the Storage Formation and Sealing Units in a Multi-layered Model - Kue-Young Kim; Weon Shik Han; Junho Oh; Eungyu Park; Pyeong-Koo Lee (Transport in Porous Media, 2014)

Phospholipase D1 is an Important Regulator of bFGF-Induced Neurotrophin-3 Expression and Neurite Outgrowth in H19-7 Cells - Hye-Jin Choi; Brian Junho Chang; Joong-Soo Han (Molecular Neurobiology, 2012)

Characteristics of Salt-Precipitation and the Associated Pressure Build-Up during CO2 Storage in Saline Aquifers - Kue-Young Kim; Weon Shik Han; Junho Oh; Taehee Kim; Jeong-Chan Kim (Transport in Porous Media, 2012)